(untitled) - Silberberg, Martin S. (Boston, 2003)
With each edition, Chemistry: The Molecular Nature of Matter and Change by Martin Silberberg is becoming a favorite among faculty and students. Silberberg's 3rd edition contains features that make it the most comprehensive and relevant text for any student enrolled in General Chemistry. The text contains unprecedented macroscopic to microscopic molecular illustrations, consistent step-by-step worked exercises in every chapter, an extensive range of end-of-chapter problems which provide engaging applications covering a wide variety of freshman interests, including engineering, medicine, materials, and environmental studies. All of these qualities make Chemistry: The Molecular Nature of Matter and Change the centerpiece for any General Chemistry course.
Keywords: Chemistry,Hóa học